"The Third Pillar: How Markets and the State Leave the Community Behind" - Adhikari, Sabitri Devi Acharya (Economic Journal of Nepal, 2021)
The Third Pillar: How Markets and the State Leave the Community Behind, Harper Collins, India, 464 pp., (Paperback) ISBN-13‏: 978-0525558316; NRs.1278.4.